The strategy of digital wholesale banking transformation: navigating the banking ecosystem - Lufina Mahadewi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
The study explores the strategy of wholesale banking’s digital transformation as a central solution for integrating the digital banking ecosystem across the entire customer-centric value chain, while addressing challenges related to the complexity of transaction structures and the relationship model. A qualitative case study of a leading wholesale bank in Indonesia is used to uncover wholesale banking digitalization strategies for a holistic transformative strategy for the banking financial ecosystem. Thematic analysis of semi-structured interviews with 16 senior executives in relationship and transaction banking managers and triangulated with bank’s reports and websites. The results reveal four thematic themes: single sign-on digital wholesale platform, omnichannel touchpoints, the use of artificial intelligence, and big data analytics. This study contributes to the theory of dynamic capabilities and open innovation by identifying the transformative and strategic dynamics of wholesale digitalization and its role in navigating the orchestration of the banking ecosystem by emphasizing the role of digital capabilities in extracting the potential value chain. This study provides a nuanced understanding of wholesale digital platform solutions for banks, serving as a reference for providing access across the entire banking ecosystem by forming partnerships within the ecosystem, leveraging artificial intelligence, personalizing transactional suites, and implementing seamless onboarding. Keywords: Digital Wholesale Banking Strategy, Digital Banking Ecosystem, Open Innovation, Dynamic Capabilities, Single Sign-On Digital Wholesale Platform, Omnichannel Touchpoints, Artificial Intelligence, Big Data Analytics